Learning scala practical functional programming for the JVM - Swartz, Jason (O'Reilly Media, 2015)
Written for programmers who are already familiar with object-oriented (OO) development, the book introduces you to the core Scala syntax and its OO models with examples and solutions that build familiarity, experience, and confidence with the language.